Digitization of Student Activity Assessment and Reporting at Kampar Polytechnic - Oktorina, Fenty Kurnia (Internet of Things and Artificial Intelligence Journal, 2025)
Students in higher education institutions are expected to actively participate in various academic and non-academic activities to develop their potential. At Politeknik Kampar, student activity records are still managed manually by the Student Affairs Administration Division (BAK), which leads to difficulties in obtaining valid and organized data. This research aims to build a Digital Assessment system of student activities at Kampar Polytechnic whose purpose is to facilitate the process of managing student participation data. Especially evaluation and reporting. The method used is the development of the System Development Life Cycle (SDLC). The programming language used in this research is PHP with the Laravel Framework, this framework is known for its good data management and accuracy and has structured data management. The result of this research is the development of an application that will focus on the process of reporting activities carried out by students directly, in real-time, and can be monitored and validated directly. With this system, it is ensured that the management of student activities can be more organized, transparent, and accessible to students, BAK, and all related parties.